The Impact of Competitive Relations on the Issuers’ Dividend Policy - ZHURBA, Oleksandr (Theoretical and Practical Research in Economic Fields, 2024)
Purpose: The aim of the research is to analyse the impact of indicators of market position and financial stability of companies as determinants of competitiveness on dividend policy. Methodology: The research employed the methods of correlation analysis, multivariate regression, and statistical analysis. Findings: As a result of the study, two indicators characterizing dividend policy and eleven indicators were identified as determinants of companies’ competitiveness. It was established which determinants of competitiveness have a close connection and significant impact on the dividend policy. It was found that for Lenovo, P/B ratio (–0.69) has the greatest impact, Dividend Yield, variables not included in the model (0.62), Annual revenue (1.18), Net assets by year (0.93) — on Annual dividend payments. For ASUS, Total debt by year (0.88) has the greatest impact on Dividend Yield, Total liabilities (0.36) and Total debt (0.63) - on Annual dividend payments. Originality: The results indicate that ASUS actively uses debt policies in the competition for investors, while Lenovo follows a more conservative approach. The results may be useful for investors when choosing companies to invest in. Research prospects may be aimed at investigating the relationship between dividend policy and global macroeconomic phenomena.